CYBERCRIME AGAINST WOMEN IT’S EVOLUTION AND EFFECTS ON PERSONAL LIFE - Vaishnav, Abhilasha; Dewan, Beena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A violation of human rights, violence against women is not a new occurrence. Throughout Indian history, it has taken several forms. In the course of history, numerous women’s rights activists campaigned against violence against women and for their empowerment society, yet her vulnerability and abuse have no bounds. Because of the information technology that revolutionised the way people communicate building a "Global Village" and ensuring that women have the same rights as men. An invention modern technology has drastically improved the lives of women throughout the world thanks to the Internet, smartphones, and tablets. Despite the fact that these innovations have provided enormous benefits for us, they are not without drawbacks. A significant impact on our daily lives and produced a significant hazard known as "Cyber Crime." Mostly, Women are frequently the targets of cybercrime because they are more vulnerable. In the absence of proof due to these factors, as well as the public’s inherent distrust of the media, catching a criminal is a difficult task. Women have been targeted by cyber-bullying with regards to online slander, sexual misconduct or abuse, pornography or the use of false or misleading email addresses etc. Women are subjected to harassing and sexually explicit phone calls and emails as a result of their harassment and expose her to public scrutiny huge, to the point where she is contemplating taking her own life. The authors of this work assume that in India, how is violence against women affecting women’s social lives? This article examines the causes and types of cyber-crime, as well as possible solutions. Women are the victims of cybercrime.